A differential game model of intrusion detection system in cloud computing. (January 2017) - Li, Zhi; Xu, Haitao; Liu, Yanzhu
The multi-mesh distributed and open structure of cloud computing is more weak and vulnerable to security threats. Intrusion detection system should be incorporated in cloud infrastructure to monitor cloud resources against security attacks. In this article, the interaction between rational cloud resource defender and the potential malicious user in the cloud as a differential game is investigated. The feedback Nash equilibrium of the game is reviewed and a complex decision-making process and interactions between the cloud resource defender and a malicious user of cloud are also analyzed. The system results support a theoretical foundation in detecting the malicious attack, which can help cloud intrusion detection system make the optimal dynamic strategies to improve the defensive ability.